Fuzzy logic controlled adaptive scheduling of public utility buses in Metro Manila - Escolano, Cyrill O. (Animo Repository, 2016)
Tactical transit planning is a crucial task in transportation industry. It mainly concentrates in the scheduling and setting of trip frequencies. One way of solving the scheduling pattern is the selection of the optimal dispatching interval of the transit system. This paper aims to create an adaptive scheduling and dispatching of public utility buses plying along EDSA. A fuzzy logic controller is designed based on the passenger and vehicle data. The self-adaptive controller will decide for the best dispatch interval of public buses from terminals based on given fuzzy sets or conditions. It seeks to choose solution in such a way that the travel time of passengers and number of buses running along EDSA are minimized while the operational constraints such as the traffic demand, departure time and maximum (minimum) headway are satisfied. The fuzzy logic controller is developed using Matlab. Effectiveness, accuracy and robustness of the system are evident in the results. © 2015 IEEE.